تحليل إنتاج البندورة ودراسة الجدوى الاقتصادية لزراعتها في البيوت البلاستيكية في الساحل السوري - يعقوب غسان (Latakia University Journal -Biological Sciences Series, 2019)
يتناول البحث دراسة الجدوى الاقتصادية لزراعة وإنتاج البندورة في البيوت البلاستيكية في الساحل السوري من خلال دراسة تحليلية اقتصادية لمشروع 18 بيت بلاستيكي (هكتار واحد) مزروع بالبندورة لمدة عشر سنوات. لقد تبين من خلال الدراسة أن 91,13% من إجمالي عدد البيوت البلاستيكية موزعة في الساحل السوري وأن نسبتها في محافظة طرطوس تحتل المرتبة الأولى وتشكل 76,62% أما في محافظة اللاذقية فتشكل 14,51% حسب إحصائيات 1999م. وبينت الدراسة أن قيمة معامل الارتباط بين السماد العضوي والإنتاج r = 0.99 والسماد المعدني والإنتاج r = 0,97 فكلاهما يعبر عن ارتباط موجب وقوي جداً. أما معادلة الانحدار بين كمية الإنتاج y والسماد العضوي x فهي y = 1,35 + 0.56 x . وبين كمية الإنتاج y والسماد المعدني x هي y = 2,17 + 0,032 x. وأن متوسط إنتاج البيت البلاستيكي الواحد 8 طن سنوياً وإن سعر الكيلو وسطياً لفترة الدراسة 15 ل.س. بينما كلفة إنتاج واحد كيلو غرام من البندورة يساوي 13.58 ل.س وكلفة إنتاج 100 ل.س تساوي 90,52 ل.س وأن معدل الدخل السنوي للمشروع 268857 ل.س ومعدل العائد العام لرأس المال = 13,75% ومعدل الربح إلى الإيرادات 12,08% وبعد حساب معدل العائد الداخلي تبين لنا أنه يساوي 12,25%. This research deals with studying the economic feasibility of tomato farming and producting in the Syrian coast, throughout an economical and analytical study of a project has 18 greenhouse (one hectare) farmed with tomato for ten years. Through the study it has been shown that about 91,13 % of the total of green-house numbers distributed in the Syrian coast. So its ratio in Tartous district comes first about 76,62 %, But in Lattakia district it comes second about 14,51% according to the statics in 1999. The study revealed the value of an organic fertilizer and the production such as: r = 0,99, also the mineral fertilizer and the production such as : r =0,97, so that both of them are of a positive and strong linkage, thus decline equation between production quantity “y”, and organic fertilizer x” is as follows y = 1,35 + 0.56 x, and between production quantity “y” and the mineral fertilizer “x” is : y = 2,17 + 0,032x. the average of one green house production is 8 tons yearly, and the average price of one kg of the studying period is 15 Syrian pounds. While the cost of producting one kilogram 100 Syrian pounds equals 90,52 Syrian pound. So the average of annual income of the project is about 268857 Syrian pounds. And the average of capital reserve equals 13,75%, the average of gain to incomes is 12,08%. After computing the internal Rate of Return equals 12,25% .